Neighbors in conflict: the territorial disputes of Mexico with Central America and Guatemala, 1823-1897 - Sánchez Andrés, Agustín (2019)
The separation of Mexico from the United Provinces of Central America in July 1823, after the fall of the First Empire, created the basis for a conflictive relationship between Mexico and Guatemala. The annexation of Chiapas and Soconusco to the Mexican Republic and the subsequent disagreements in the layout of the border, after the independence of Guatemala from the Central American Federation in 1839, tensed bilateral relations until the signing of theHerrera-Mariscal Treaty in 1882, although the problem would not be definitively solved until the conclusion of the works of delimitation in 1897.